Beyond the 90‐90‐90: refocusing HIV prevention as part of the global HIV response. Issue 1 (19th December 2016) - Baggaley, Rachel; Dalal, Shona; Johnson, Cheryl; Macdonald, Virginia; Mameletzis, Ioannis; Rodolph, Michelle; Figueroa, Carmen; Samuelson, Julia; Verster, Annette; Doherty, Meg; Hirnschall, Gottfried
Abstract : Introduction: The remarkable expansion in availability of antiretroviral therapy (ART) over the past two decades has transformed HIV infection into a manageable chronic condition. People with HIV infection now live long and healthy lives on treatment that is simpler, safer and cheaper. According to UNAIDS estimates, the global coverage of ART reached 46% in 2015, resulting in a 26% decrease in annual HIV‐related deaths since 2010. Such success has positioned treatment access at the centre of the global HIV response as a way to prevent mortality, morbidity and HIV transmission through a "Treat All" approach. Continuing expansion of treatment is needed to further reduce HIV‐related mortality. This progress with treatment, however, masks a stagnation in the estimated annual number of new HIV infections. Continuing levels of HIV incidence despite treatment scale‐up stem from several factors, which should be addressed in order to prevent new infections and decrease the numbers of people requiring treatment in the future. Discussion: ART can only reach those already diagnosed, and although it is unclear what proportion of new infections occur during acute and early infection prior to treatment initiation, phylogenetic studies suggest that it might be substantial. Thus, better testing approaches to reach the 40% of people with undiagnosed HIV infection as early as possible are critical. New approaches to reach men, young people and key populations, where HIV risk is highest and HIV prevention, testing and treatment coverage is lowest, are also needed. Overall coverage of effective prevention interventions remains low, enabling HIV transmission to occur, or time is required to show population‐level effects. For example, the full impact of the medical male circumcision intervention will be seen once a larger proportion of men in age cohorts with high incidence are circumcised. Finally, strategically focused pre‐exposure prophylaxis interventions have the potential to prevent HIV acquisition among populations at substantial risk, averting treatment costs in coming years. Conclusions: The United Nations (UN) targets to end AIDS include the "90‐90‐90" targets for HIV diagnosis, treatment and viral suppression. While 90‐90‐90 has been widely emphasized and adopted by countries and international funders, the focus thus far has largely been on increasing access to ART – the second "90." A similar emphasis on achieving UN HIV prevention targets and adequate funding for meeting these is essential, alongside treatment, in order to reduce population‐level incidence and change the trajectory of the HIV epidemic over the long term.